"Right reason" and the Princeton mind : an unorthodox proposal - Helseth, Paul Kjoss, 1962- (Phillipsburg, N.J. : P&R Pub., 2010)
"Were Machen and his predecessors at old Princeton Seminary really the purveyors of an essentially humanistic philosophy rather than the champions of Reformed orthodoxy? Was the driving force behind their theological labors, in other words, an understanding of religious epistemology that supplants the epistemological assumptions of the Reformed tradition with those of an 'alien philosophy'? The study...is grounded in the conviction that the reigning (or 'orthodox') interpretation of the Princeton theology cannot stand because it ignores the moral rather than the merely rational nature of the Princetonians' thought. The author suggests that old Princeton's religious epistemology is compatable with the assumptions of the Reformed tradition because its emphasis on 'right reason' is moral rather than merely rational" -- Book Introduction.
Foreword / John D. Woodbridge -- The moral context -- A "rather bald rationalism"? -- The task of Christian scholarship -- The critique of theological liberalism -- "Re-imagining" the Princeton mind -- Theological aesthetics at old Princeton Seminary -- Conclusion: The role and function of doctrine.
Includes bibliographical references (p. 223-247) and index.
Keywords: Princeton Theological Seminary; Faith and reason -- Christianity; Knowledge, Theory of (Religion); Reformed epistemology